MODERN ISLAMIC BOARDING SCHOOL CURRICULUM AND ITS EXAMPLE IN SAMBAS (PONPES MUHAMMAD BASUNI IMRAN) - Khairul Fikri; Suhana Sarkawi; Mowafg Masuwd (CV. Adiba Aisha Amira, 2024)
This article was prepared with the aim of discussing the curriculum of modern Islamic boarding schools and an example of this is in Sambas district, namely, Muhammad Basuni Imran Islamic boarding school. By using the research library research method, the research results show that Muhammad Basuni Imran Islamic Boarding School refers to the Minister of Religion Decree Number 183 of 2019 concerning Islamic Education and Arabic Curriculum in Madrasah that the PAI and Arabic language curriculum in madrasah is gradually directed towards preparing students who have competence in understanding the principles of the Islamic religion, both related to moral beliefs, sharia and the development of Islamic culture, thus enabling students to carry out their religious obligations properly regarding their relationship with Allah SWT as well as fellow humans and the universe.